EVALUASI PENAMPILAN KARAKTER HORTIKULTURA BEBERAPA GENOTIPE JAGUNG DAN POTENSINYA UNTUK DIKEMBANGKAN SEBAGAI JAGUNG SEMI (Baby Corn) - Marlina Sirait; Surjono H. Sutjahjo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
The objective of this study was evaluate horticultural performance of several maize genotypes and their potential to be developed as baby corn. The experiment was conducted at Sindangbarang Experimental Station of Bogor Agricultural University Bogor, from April until June 1995. The design used was randomized complete block design (RED) with three replications. Fifteen genotypes consisted of local maize (8 numbers), improved variety (3 numbers) and introduction (3 numbers) were evaluated with CP1-1 hybrid which has been usual in producing baby corn was used as control variety. The result showed that the introduced genotypes CM-90 and SPLC6 gave highest number of baby corn with yield of 2.60 ear per plant (equivalent to 3.04; ton/ha) and 2.20 ear per plant (equivalent to 3.04 ton/ha), respectively, while CP1-1 hybrid only produced 1.80 ear per plant (equivalent to 1.72 ton/ha). Therefore, CM-90 and SPLC6 were found to have higher yield of marketable baby corn than the control variety. Considering days to harvest of baby corn, CM-90 (56.05 dap)was found earlier than SPLC6 (61.60 dap).